Joint optimization of system utility in UAV-enabled edge computing - Huaiyu Zuo; Erqing Zhang; Yulong Tang; Mengxia Yin; Wu Dong (PLoS ONE, 2026)
This paper addresses the joint optimization of system utility in Unmanned Aerial Vehicle (UAV)-enabled Mobile Edge Computing (MEC) networks. Unlike traditional approaches that optimize individual components, such as users, UAVs, or base stations, we propose a novel framework aimed at maximizing the overall system utility, which is defined as the difference between the total revenue of service providers (UAVs and base stations) and the total cost incurred by users. The proposed model incorporates realistic constraints, including limited computational resources and energy consumption, and formulates the problem as a Mixed-Integer Nonlinear Programming (MINLP) model. To solve this complex optimization problem, we develop an efficient algorithm that integrates the Block Successive Upper-Bound Minimization (BSUM) framework with heuristic methods, enabling the decomposition of the original problem into tractable subproblems that are solved iteratively. Simulation results demonstrate that the proposed approach significantly outperforms traditional heuristic algorithms in terms of system utility, while also exhibiting robust convergence and reliability across various network configurations. The results highlight the effectiveness of joint optimization in improving both the economic and operational efficiency of UAV-assisted MEC systems, providing a solid foundation for future research in network utility management.